Evidence of reduced vertical transmission of Neospora caninum associated with higher IgG1 than IgG2 serum levels and presence of IFN-γ in nonaborting chronically infected cattle under natural condition - Pereyra, Walter Rodrigo (2019)
Neospora caninum infection of cattle can be vertically transmitted, resulting in abortion or birth of infected calves. Vertical transmission occurs both in acutely or chronically infected cattle. There is little information on the immune response needed to prevent endogenous transplacental transmission, particularly from chronically infected cattle to their offspring in a natural environment. In this study, N. caninum seropositive pregnant cattle from three different farms with high avidity antibodies and low IgM titers were selected and their newborn colostrum-deprived calves were tested for anti-N. caninum antibodies. Based on these results, dams were grouped according to their congenital transmission status. The analysis of the immune profile of the chronically-infected pregnant cattle revealed that higher ratio between IgG1 and IgG2 anti-N. caninum serum titers and higher levels of systemic IFN-γ were associated with diminished vertical transmission rates, compared to dams with the opposite profile. Our results evidenced an association between the immune profile and vertical transmission in nonaborting chronically infected dams, and confirm that vertical transmission, even when not leading to abortion, is related to a defined immune profile. This is important information to accomplish successful vaccine development efforts.